Blood lipids in middle-aged British men. - Thelle, D S (1983)
The concentrations of serum total cholesterol, high density lipoprotein-cholesterol, and triglycerides have been measured in 7735 men aged 40 to 59 years who were drawn from general practices in 24 towns in England, Wales, and Scotland. The distribution of these blood lipids, their interrelations and their association with age, social class, body mass index, cigarette smoking, alcohol intake, and physical activity at work have been examined. Body mass index emerges as the factor most strongly associated with these three blood lipids. Serum total cholesterol increased with increasing body mass index until about 28 kg/m2 but thereafter showed no further rise. The relation between body mass index and high density lipoprotein-cholesterol was negative and linear; that between body mass index and triglycerides was positive and linear. The inverse relation between high density lipoprotein-cholesterol and triglycerides was independent of the fact that both were related to body mass index. Alcohol intake was associated with increased high density lipoprotein-cholesterol concentrations and cigarette smoking with lowered high density lipoprotein concentrations; the association with alcohol appeared to be dominant. No significant trends with age were observed for the three blood lipids. In this population, body mass index is closely associated with the concentration of blood lipids but its effects are probably indirect and mediated by a complex of dietary and other factors.